OP74 Stoma Cover Use By Fully Laryngectomized Patients. (2019) - Deblois, Simon; L'Espérance, Sylvain; Coulombe, Martin; Lepanto, Luigi; Rhainds, Marc
Abstract : Introduction: The use of stoma covers has been a common clinical practice for laryngectomized patients for several years. In the province of Québec, Canada, laryngectomized patients can obtain stoma covers through a dedicated program providing them with medical supplies and voice re-education services. For many years, the program's supply has included cloth and/or foam covers, but the supply of Heat and Moisture Exchangers (HME) has been limited. Two hospital-based HTA units joined their expertise to assess the opportunity of providing HMEs to more patients, depending on their clinical characteristics. Methods: Their joined assessment rested on a systematic review (SR) and a field assessment. The systematic review aimed at assessing the efficacy, clinical effectiveness and safety of various types of stoma covers. The field inquiries intended to assess the perceptions of clinicians and managers towards stoma covers in clinical practice. Results: We included 27 studies in the SR. Most of them appraised the clinical effectiveness or safety of HME filters. Their methodological quality was very low with potential conflicts of interest whereas many studies were financed by the industry. The heterogeneity of study designs, expected outcomes and paucity of comparative studies prevented the pooling of results. Industry sponsorship appeared to be an important issue, since 17 of the included studies were sponsored. The SR did not provide conclusive evidence concerning the efficacy, clinical effectiveness and safety of the various types of stoma covers. The field inquiries intended to assess the perceptions of clinicians and managers towards stoma covers in clinical practice. It showed that industry representatives are quite active in clinical settings, promoting their products. Clinicians' opinions and preferences were coherent with the systematic review main observations: in a context where the quality of the evidence is low, clinicians' recommendations of stoma protectors for laryngectomies are mainly based on their professional experience and academic training. Conclusions: Future research of high methodological quality would strengthen the evidence concerning the relative efficacy and safety of different stoma protectors. These studies would help define evidence-based allocation criteria and set parameters so that the choice of a stoma protector is best adapted to a laryngectomized patients' condition.